2011
DOI: 10.1007/s00127-011-0354-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of social factors including trust, control over life decisions, problems with transport and safety, to psychological distress in the community

Abstract: PurposePsychological distress encompasses anxiety and depression with the previous studies showing that psychological distress is unequally distributed across population groups. This paper explores the mechanisms and processes which may affect the distribution of psychological distress, including a range of individual and community level socioeconomic determinants.MethodsRepresentative cross-sectional data was collected for respondents aged 16+ from July 2008 to June 2009, as a part of the South Australian Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…We reverse-coded items so that higher scores indicate more control. These items have been used in previous research studies and found to be reliable (Cronbach's alpha ¼ 0.83) (Taylor et al, 2012(Taylor et al, , 2017Kim et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…We reverse-coded items so that higher scores indicate more control. These items have been used in previous research studies and found to be reliable (Cronbach's alpha ¼ 0.83) (Taylor et al, 2012(Taylor et al, , 2017Kim et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that longer practice of a TCC program improves a person's anxiety level; however, the participants still have minimal anxiety levels after the intervention. Research has indicated that decreasing anxiety increases a person's energy, improves quality of life, 29 and enhances memory and cognition functions, 30 as well as reducing time pressure, 29 information overload, 30 negative thinking, 5 and smoking behavior. 31…”
Section: Anxietymentioning
confidence: 99%
“…Gender also contributes with women reporting poorer mental health compared to men across the socioeconomic gradient [ 6 ], which may be due to the unequal distribution of power between men and women, as well as between the least and most educated individuals. Feeling a lack of control over one’s life is an important social determinant of health [ 9 ] and risk factor for depression [ 10 ], and powerlessness related to the traditional gender roles of employment, care-giving, and housekeeping may exacerbate psychological distress [ 11 ]. Furthermore, the impact of unemployment on mental health is stronger for men compared to women, but likely influenced by family responsibilities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%